1998
DOI: 10.1001/archsurg.133.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Factors Associated With Postoperative Pulmonary Complications Following General Elective Surgery

Abstract: To develop a predictive model identifying perioperative conditions associated with postoperative pulmonary complications (PPCs).Design: A prospective survey of patients whose preoperative history and physical examination, spirometric, PaO 2 and PaCO 2 analysis, and operative results were recorded. These patients underwent postoperative cardiopulmonary examinations until they were discharged from the hospital; their medical records were also reviewed until they were discharged from the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(95 citation statements)
references
References 42 publications
6
79
1
8
Order By: Relevance
“…7 The aim of this study is to review our experience with supracricoid and supraglottic laryngectomies at our Institution over a 20 years period in a series of 416 consecutive patients, to investigate possible PP risk factors. Since several reports from other districts 8,9 suggest a possible PP prognostic significance, we also investigated the prognostic role of PP in our series.…”
Section: Introductionmentioning
confidence: 99%
“…7 The aim of this study is to review our experience with supracricoid and supraglottic laryngectomies at our Institution over a 20 years period in a series of 416 consecutive patients, to investigate possible PP risk factors. Since several reports from other districts 8,9 suggest a possible PP prognostic significance, we also investigated the prognostic role of PP in our series.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfactory results of epidural anesthesia as an adjunct to general anesthesia have encouraged practicing regional anesthesia solely in patients with severe pulmonary diseases (6). Retrospective and prospective studies have shown that it is possible to preserve the pulmonary functions in patients with severe COPD, using neuroaxial blockade instead of general anesthesia, as good as in patients with no pulmonary dysfunction (7)(8)(9). Functional residual capacity is reduced following abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The highest risk of respiratory complications is in patients undergoing thoracic or upper abdominal operations (603)(604)(605)(606)608), and the risk might be expected to be lower in the patient having a kidney transplant. By multivariate analysis, risk factors for postoperative pulmonary complications that developed in 11.8% of adult, male recipients undergoing elective abdominal surgery, were postoperative nasogastric suction, preoperative sputum production and longer duration of anesthesia (613). In another multivariate analysis (after controlling for type of surgery, duration of anesthesia and other risk factors) current cigarette smokers were 5.5 times more likely to develop pul- monary complications compared to those who didn't smoke (614).…”
Section: Pulmonarymentioning
confidence: 96%